2001
DOI: 10.1074/jbc.m103819200
|View full text |Cite
|
Sign up to set email alerts
|

SNIP1 Inhibits NF-κB Signaling by Competing for Its Binding to the C/H1 Domain of CBP/p300 Transcriptional Co-activators

Abstract: SNIP1 is a 396-amino acid nuclear protein shown to be an inhibitor of the TGF-␤ signal transduction pathway and to be important in suppressing transcriptional activation dependent on the co-activators CBP and p300. In this report we show that SNIP1 potently inhibits the activity of NF-B, which binds the C/H1 domain of CBP/ p300, but does not interfere with the activity of transcription factors such as p53, which bind to other domains of p300, or factors such as VP16, which are independent of these co-activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 53 publications
5
70
1
1
Order By: Relevance
“…Together, these results demonstrate that SNIP1 is an important cellular regulator of cell proliferation and the cell cycle, functionally linked to known oncogenes. SNIP1 had previously been identified as a p300 coactivator interacting protein (Kim et al, 2000(Kim et al, , 2001 and our studies were originally initiated to further investigate the functional significance of this observation. Although we verified the interaction of SNIP1 with p300 in NMuMg cells, we did not observe this interaction in the U-2 OS cells used in many of our experiments (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these results demonstrate that SNIP1 is an important cellular regulator of cell proliferation and the cell cycle, functionally linked to known oncogenes. SNIP1 had previously been identified as a p300 coactivator interacting protein (Kim et al, 2000(Kim et al, , 2001 and our studies were originally initiated to further investigate the functional significance of this observation. Although we verified the interaction of SNIP1 with p300 in NMuMg cells, we did not observe this interaction in the U-2 OS cells used in many of our experiments (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies revealed that SNIP1 also interacts with the C/H1 domain of the transcriptional coactivators p300 and CREB binding protein (CBP) (Kim et al, 2000), which functions as a binding site for many transcriptional regulators (Goodman and Smolik, 2000). Through this interaction, SNIP1 overexpression was shown to inhibit the activity of the RelA(p65) nuclear factor-kB (NF-kB) subunit and displace binding of Smad4 to this domain (Kim et al, 2000(Kim et al, , 2001. Therefore, SNIP1 has the potential to function as a regulator of many transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, transfection of HAtagged SNIP1 deletion mutants revealed that the interaction was specific for the FHA-domain containing C-terminal region of SNIP1 (Figure 5b). By comparison, it is the N-terminal region of SNIP1 that has been previously shown to interact with the p300 coactivator and bind RelA in vitro (Kim et al, 2000(Kim et al, , 2001. Importantly, gel filtration analysis demonstrated that neither ATR nor Chk1 is present in the high-molecularweight SNIP1 complex we identified previously (Roche et al, 2004) (Figure 5c), suggesting that this interaction is weak and likely to be transient.…”
Section: Snip1 Associates With Atrmentioning
confidence: 90%
“…SNIP1 has previously been implicated as a regulator of NF-kB through binding p300 (Kim et al, 2001). SNIP1 has also been reported to bind directly to the Rel homology domain (RHD) of RelA (Kim et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation